THE PROBLEM OF FINDING THE WAYS OF EDUCATION MORAL PERSONALITY AT THE PRESENT STAGE DEVELOPMENT OF UKRAINIAN SOCIETY CONTEXTS OF USING PHILOSOPHICAL OF PEDAGOGICAL EXPERIENCE OF DOMESTIC THINKERS OF THE SECOND HALF OF THE XVIII CENTURY (Pedagogy of Higher and Secondary Education, 2007)
In clause the base principles of education of the moral person are considered by use of pedagogical experience Ukrainian scientists second half XVIII of century.